The Portrait of Local Wisdom Values in Constructing Character Education Management in Indonesia - Tri Setyo; Sri Minarti; Ahmad Fauzi (IAIN Ponorogo, 2021)
This study aims to interpret the value of local madrasa wisdom. Habitualization of these values is then used as social capital in building a character education management paradigm. It is based on various problems faced in Islamic education management. Thus, to provide a holistic and in-depth understanding, this research used a qualitative approach with the social construction theory of Peter L. Berger. It was through the dialectical relationship between externalization, objectivation, and internalization. This study found that 1) madrasa local wisdom is essentially a manifestation of the Qur'an as a (belief system) and becomes the basis for managing Islamic education; 2) madrasa local wisdom, such as; honesty, discipline, togetherness, commitment, simplicity, independence, sincerity, leadership, hard work, and responsibility, understood as positive energy and internalized in the madrasa environment; 3) habitualization of the value of local wisdom of madrasa, is a social capital which is then transmitted in the management of Islamic education so that it can influence all practical individual social thoughts and actions in the organization. Penelitian ini bertujuan untuk menginterpretasikan dan memaknai nilai kearifan lokal madrasa, habitualisasi nilai tersebut kemudian dijadikan sebagai modal sosial dalam membangun paradigma manajemen pendidikan karakter, hal ini didasarkan atas pelbagai persoalan di bidang pengelolaan pendidikan Islam baik secara fondasional maupun operasional dan belum terselesaikan. Demikian untuk memberikan pemahaman secara holistik dan mendalam, penelitian ini menggunakan pendekatan kualitatif dengan teori konstruksi sosial Peter L. Berger, melalui hubungan dialektis antara eksternalisasi, objektivasi dan internalisasi. Penelitian ini menghasilkan beberapa temuan; 1) kearifan lokal madrasa pada hakikatnya merupakan manifestasi dari al-Qur’an sebagai (belief system) dan menjadi dasar pengelolaan pendidikan Islam; 2) kearifan lokal madrasa, seperti; kejujuran, kedisiplinan, kebersamaan, komitmen, kesederhanaan, kemandirian, keikhlasan, kepemimpinan, bekerja keras dan tanggung jawab, difahami sebagai energi positif dan di internalisasikan dalam lingkungan madrasa; 3) habitualisasi nilai kearifan lokal madrasa, merupakan sebuah modal sosial (social capital) yang kemudian ditransmisikan dalam pengelolaan pendidikan Islam, sehingga dapat mempengaruhi seluruh pemikiran dan tindakan sosial individu yang efektif dalam organisasi.